Diseño del Sistema de Gestión Integrado basado en las normas ISO 9001:2015 y el Decreto 1072:2015; libro 2 parte 2 titulo 4to capitulo 6 en la empresa CESALUD S.A (2016)
This document is based on the design of integrated management system based on ISO 9001: 20015 and Decree 1072/15; Book 2 Part 2 Chapter 6 in the 4th title company Cesalud S.A. as a management tool for the achievement of corporate goals promoting continuous improvement in processes.